Application of HBF with Adaptive Port Mapping for LEO Satellite Communication Systems - Semernya, Roman; Xueliang, Shi; Lyashev, Vladimir; Revutsky, Vadim; Yue, Zhou; Lei, Dong (IEEE Vehicular Technology Conference, 2021)
Based on maritime and airline routes traffic given by automatic dependent surveillance (ADS) real data and population distribution model we assumed that asymmetric user distribution scenarios could be quite often in LEO satellite communication systems. To increase payload flexibility in such scenarios we have proposed simple partially connected (PC) hybrid phase array antenna (HPAA) architecture with adaptive port mapping (APM) based on predefined structures and showed that it significantly outperforms conventional PC architectures with fixed port mapping configurations. Due to low number of RF switches proposed architecture provides low complexity solution for LEO satellites comparing to the APM architectures with full connection RF switch matrix. System capacities of proposed and conventional architectures were tested and compared for MU-MIMO downlink transmission using joint scheduler and simple hybrid beamforming (HBF) algorithm with sectorizing analog precoder based on DFT codebook and digital precoder based on ZF. Simulation results showed that APM architecture provides more capacity gain for scenarios with higher asymmetrical UE distributions.